Association between dyslexia and overweight/obesity among Chinese children: findings from a cross-sectional study - Zhu, Bing; Fan, Hong; Wang, Min; Zhu, Kaiheng; Feng, Yanan; Wang, Haoxue; Jiang, Qi; Xiang, Zhen; Chen, Qianhui; Xiong, Ziyan; Song, Ranran (Frontiers in Pediatrics, 2025)
BackgroundExtensive studies have consistently reported associations between neurodevelopmental disorders and overweight/obesity. However, limited research addressed the weight status of children with dyslexia. Therefore, this study aimed to explore the association between dyslexia and overweight/obesity among Chinese children.Methods7,116 children were recruited from the Tongji Reading Environment and Dyslexia research program, including 197 dyslexic and 6,919 non-dyslexic children. The standard “Screening for overweight and obesity among school-aged children and adolescents (WS-T 586-2018)” was utilized to define overweight and obesity. Logistic regression models were employed to examine the association between dyslexia and overweight/obesity.ResultsAmong dyslexic children, 18.8% were overweight and 23.9% were obese. Among non-dyslexic children, 17.3% were overweight and 15.4% were obese. The proportion of obesity among dyslexic children was significantly higher than that among non-dyslexic children (P = 0.001). After adjusting for all potential confounders, children with dyslexia were more likely to be obese (OR = 1.57, 95% CI: 1.10-2.24). Analyses stratified by sex indicated that such associations were more significant among girls. No significant association was found between dyslexia and overweight.ConclusionsThis cross-sectional study provides evidence that dyslexic children had significantly higher odds of obesity. This finding emphasizes the urgent need for heightened awareness and strategies targeted to mitigate excess body weight for this special population.